Awareness of dental practitioners to cope with a medical emergency: a survey in Belgium. (26th June 2013) - Marks, Luc A. M.; Van Parys, Celine; Coppens, Marc; Herregods, Luc
<x xml:space="preserve">Abstract</x> Objective The aim of the study is to determine whether in Belgium dentists feel confident to diagnose a medical emergency situation in their dental practice. Methods A questionnaire was completed by 7.0% of the active Belgian general dental practitioners (n = 548) including questions on the frequency and knowledge of medical emergency situations in the dental office, history of dental training to treat emergency situations and confidence level in treating emergency situations. Results A medical history of each patient was taken by 55.3% of the dentists. A link was found between years since graduation and the systematic decline of a medical history in a new patient (P = 0.001): the older the dentist, the less consistent was the updating of medical history. Almost 50% of the dentists (49.4%) never participated in any basic life support (BLS) training during their undergraduate education. Moreover, 78.3% never had any paediatric BLS training during undergraduate education and BLS training after graduation was lacking by 37.2% of the dentists. Conclusion Knowledge of BLS should be fundamental to medical professionals. The more BLS training a practitioner has experienced, the more self‐secure they feel coping with an emergency situation.